Identification and quantification of oleanane triterpenoid saponins and potential analgesic and anti-inflammatory activities from the roots and rhizomes of Panax stipuleanatus - Shu, Pan-Pan (J Ginseng Res, 2021)
BACKGROUND: Panax stipuleanatus represents a folk medicine for treatment of inflammation. However, lack of experimental data does not confirm its function. This article aims to investigate the analgesic and anti-inflammatory activities of triterpenoid saponins isolated from P. stipuleanatus. METHODS: The chemical characterization of P. stipuleanatus allowed the identification and quantitation of two major compounds. Analgesic effects of triterpenoid saponins were evaluated in two models of thermal- and chemical-stimulated acute pain. Anti-inflammatory effects of triterpenoid saponins were also evaluated using four models of acetic acid–induced vascular permeability, xylene-induced ear edema, carrageenan-induced paw edema, and cotton pellet–induced granuloma in mice. RESULTS: Two triterpenoid saponins of stipuleanosides R(1) (SP-R(1)) and R(2) (SP-R(2)) were isolated and identified from P. stipuleanatus. The results showed that SP-R(1) and SP-R(2) significantly increased the latency time to thermal pain in the hot plate test and reduced the writhing response in the acetic acid–induced writhing test. SP-R(1) and SP-R(2) caused a significant decrease in vascular permeability, ear edema, paw edema, and granuloma formation in inflammatory models. Further studies showed that the levels of inflammatory mediators, nitric oxide, malondialdehyde, tumor necrosis factor-α, and interleukin 6 in paw tissues were downregulated by SP-R(1) and SP-R(2). In addition, the rational harvest of three- to five-year-old P. stipuleanatus was preferable to obtain a higher level of triterpenoid saponins. SP-R(2) showed the highest content in P. stipuleanatus, which had potential as a chemical marker for quality control of P. stipuleanatus. CONCLUSION: This study provides important basic information about utilization of P. stipuleanatus resources for production of active triterpenoid saponins.